A High‐Performance Primary Nanosheet Heterojunction Cathode Composed of Na0.44MnO2 Tunnels and Layered Na2Mn3O7 for Na‐Ion Batteries. Issue 7 (3rd March 2020) - Zheng, Peng; Su, Jiaxin; Wang, Yibing; Zhou, Wei; Song, Jiajia; Su, Qinmei; Reeves‐McLaren, Nik; Guo, Shouwu
Abstract: Owing to its large capacity and high average potential, the structure and reversible O‐redox compensation mechanism of Na2 Mn3 O7 have recently been analyzed. However, capacity fade and low coulombic efficiency over multiple cycles have also been found to be a problem, which result from oxygen evolution at high charge voltages. Herein, a Na0.44 MnO2 ⋅ Na2 Mn3 O7 heterojunction of primary nanosheets was prepared by a sol‐gel‐assisted high‐temperature sintering method. In the nanodomain regions, the close contact of Na0.44 MnO2 not only supplies multidimensional channels to improve the rate performance of the composite, but also plays the role of pillars for enhancing the cycling stability and coulombic efficiency; this is accomplished by suppressing oxygen evolution, which is confirmed by high‐resolution (HR)TEM, cyclic voltammetry, and charge/discharge curves. As the cathode of a Na‐ion battery, at 200 mA g −1 after 100 cycles, the Na0.44 MnO2 ⋅ Na2 Mn3 O7 heterojunction retains an 88 % capacity and the coulombic efficiency approaches 100 % during the cycles. At 1000 mA g −1, the Na0.44 MnO2 ⋅ Na2 Mn3 O7 heterojunction has a discharge capacity of 72 mAh g −1 . In addition, the average potential is as high as 2.7 V in the range 1.5–4.6 V. The above good performances indicate that heterojunctions are an effective strategy for addressing oxygen evolution by disturbing the long‐range order distribution of manganese vacancies in the Mn‐O layer. Abstract : Pillar of strength : In the heterojunction of primary nanosheets, Na0.44 MnO2 plays the role of pillars for suppressing oxygen evolution of Na2 Mn3 O7 during the sodiation/desodiation process, which allows the composite to display good cycle stability (after 100 cycles, 88 % capacity is maintained) and high coulombic efficiency (approaches 100 % during the cycles).